2015
DOI: 10.1053/j.gastro.2015.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Genetic Biomarkers in Sporadic Colorectal Cancer

Abstract: Sporadic colorectal cancer (CRC) is a somatic genetic disease in which pathogenesis is influenced by the local colonic environment and the patient’s genetic background. Consolidating the knowledge of genetic and epigenetic events that occur with initiation, progression, and metastasis of sporadic CRC has identified some biomarkers that might be utilized to predict behavior and prognosis beyond staging, and inform treatment approaches. Modern next generation sequencing of sporadic CRCs has confirmed prior ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
389
3
18

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 371 publications
(416 citation statements)
references
References 149 publications
(230 reference statements)
6
389
3
18
Order By: Relevance
“…The primary molecular pathways involved in CRC carcinogenesis are chromosomal instability (CIN), microsatellite instability (MSI) and CpG island methylator phenotype (CIMP), accounting for nearly 85, 15 and 10-40% of all sporadic cases, respectively [2,3]. CIN and MSI represent two levels of genetic instability, a subtle one affecting only DNA sequences, MSI-high (MSI-H), and a gross one, affecting portions or entire chromosomes, i.e., CIN.…”
Section: Introductionmentioning
confidence: 99%
“…The primary molecular pathways involved in CRC carcinogenesis are chromosomal instability (CIN), microsatellite instability (MSI) and CpG island methylator phenotype (CIMP), accounting for nearly 85, 15 and 10-40% of all sporadic cases, respectively [2,3]. CIN and MSI represent two levels of genetic instability, a subtle one affecting only DNA sequences, MSI-high (MSI-H), and a gross one, affecting portions or entire chromosomes, i.e., CIN.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes 1 and 2 (CIMP-high, consisting 20% of CRC cases) may miss APC mutation; opposite to this, APC loss characterizes genotypes 3 to 5 (8). Only half of the hypermutated colon cancers hold the mutation, percentage significantly lower compared to respective in the nonhypermutated ones (80%) (28). Moreover, experimental findings from transgenic mice showed that colorectal tumorigenesis can be initiated in the absence of APC or β-catenin mutation (29).…”
Section: Questions Associated With the Current Model Of Colorectal Tumentioning
confidence: 99%
“…The age-dependent increase in CRC development is associated with a multistep oncogenesis process and a number of histological stages, reflecting the accumulation of genetic errors in somatic cells over time. Sporadic CRC is currently thought to arise via 1 of 3 identified molecular pathways (Micro Satellite instability-MSI, Chromosomal Instability-CIN and CpG island methylator phenotype-CIMP) depending upon the individual's complement of gene alterations [13]. Conversely, the inheritance of germline mutations may also result in development of neoplasms at an early age, with approximately 5% of CRC cases being due to inherited single-gene syndromes such as familial adenomatous polyposis (FAP) and hereditary non-polyposis colorectal cancer (HNPCC) [14].…”
Section: Introductionmentioning
confidence: 99%